KEEFEKTIVAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN EKONOMI BERBASIS KONSTRUKTIVIS TERHADAP HASIL BELAJAR SISWA - Amaludin, Asep (Dinamika Pendidikan, 2010)
Learning is a process of changing the behavior through experience and training. The changing of behavior involves knowledge, skills, attitudes and even all aspects of the organism or individual himself. Unfortunately, many students have difficulty in understanding the abstract concepts of a subject. Therefore, we need the alternative learning model to overcome the difficulties in learning. One of the learning models is Student Team Achievement Division (STAD) learning model. STAD model is a cooperative learning model encouraging students to actively discover knowledge through the skills process. The objective of this study is to determine the average difference of studentsâ learning outcomes through cooperative learning model with STAD type and the expository model on the subject material of Market Price Formation. The population of this study was all VIII Classes of SMP Negeri 1 Randudongkal in the academic year of 2007/2008. There were 7 classes consisted of 292 students. Samples are taken randomly, the first group was VIIIC students as the experimental group using STAD learning model, whereas the second group was students in VIIID class as the control group. Data was collected by test method, and then analyzed by the mean difference test. The results showed that there was a significant mean difference in studentsâ learning outcomes. The average score for experimental group was 75.93 and for the control group was only 71.36. Based on this study, it is suggested to use STAD learning model based on constructivism in teaching and learning process because it can encourage students to be active with their own skills.Â